2010
DOI: 10.1152/ajpcell.00359.2009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the extracellular matrix and integrins on volume-sensitive osmolyte anion channels in C2C12 myoblasts

Abstract: The purpose of this study was to determine whether extracellular matrix (ECM) composition through integrin receptors modulated the volume-sensitive osmolyte anion channels (VSOACs) in skeletal muscle-derived C2C12 cells. Cl(-) currents were recorded in whole cell voltage-clamped cells grown on laminin (LM), fibronectin (FN), or in the absence of a defined ECM (NM). Basal membrane currents recorded in isotonic media (300 mosmol/kg) were larger in cells grown on FN (3.8-fold at +100 mV) or LM (8.8-fold at +100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
(43 reference statements)
2
5
0
Order By: Relevance
“…We found here that the treatment of astrocyte cultures with laminin reduces the rate at which water enters these cells following a hypoosmotic challenge and in the final volume attained by these cells at the end of the challenge period, and showed that this held true whether laminin was provided in the culture substrate, or overlaid onto the cultures, and that collagen did not elicit a similar result (Figure ), thereby demonstrating that this effect was not due to the cells being encaged by the ECM networks, and that it was specific to laminin alone. It is however challenging to determine how much of this suppressive effect is due to a laminin‐mediated downregulation of AQP4 activity, as AQP4‐null astrocytes do not swell to nearly the same extent as normal cells (data not shown), especially given the fact that laminin is known to potentiate the response of hypoosmoticity‐activated volume‐sensitive osmolyte anion channels (VSOACs) as well, causing regulatory volume decrease (RVD) to occur sooner (Neveux, Doe, Leblanc, & Valencik, ). There also exists the possibility that laminin could cause a downregulation of sulfonylurea receptor 1‐transient receptor potential melastatin 4 (SUR1‐TRPM4), a two‐component ion channel that was recently shown to be expressed in response to CNS injury, and which complexes with AQP4 to mediate astrocytic swelling by facilitating the coupling of the influx of water and ions (Stokum et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We found here that the treatment of astrocyte cultures with laminin reduces the rate at which water enters these cells following a hypoosmotic challenge and in the final volume attained by these cells at the end of the challenge period, and showed that this held true whether laminin was provided in the culture substrate, or overlaid onto the cultures, and that collagen did not elicit a similar result (Figure ), thereby demonstrating that this effect was not due to the cells being encaged by the ECM networks, and that it was specific to laminin alone. It is however challenging to determine how much of this suppressive effect is due to a laminin‐mediated downregulation of AQP4 activity, as AQP4‐null astrocytes do not swell to nearly the same extent as normal cells (data not shown), especially given the fact that laminin is known to potentiate the response of hypoosmoticity‐activated volume‐sensitive osmolyte anion channels (VSOACs) as well, causing regulatory volume decrease (RVD) to occur sooner (Neveux, Doe, Leblanc, & Valencik, ). There also exists the possibility that laminin could cause a downregulation of sulfonylurea receptor 1‐transient receptor potential melastatin 4 (SUR1‐TRPM4), a two‐component ion channel that was recently shown to be expressed in response to CNS injury, and which complexes with AQP4 to mediate astrocytic swelling by facilitating the coupling of the influx of water and ions (Stokum et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although experimentally this channel is often activated by osmotic cell swelling, various pathways seem to exist that can open VRAC under isotonic conditions (29 -32). These include the involvement of signaling by integrins (46) and RhoA (47), which also play important roles in myogenesis (3). The pathways leading to the activation of VRAC during myoblast differentiation remain to be explored.…”
Section: Functional Vrac Is Required For Normal Myoblast Differentiationmentioning
confidence: 99%
“…The composition of the extracellular matrix modulates the characteristics of ICl swell through integrin receptors, and knock-down of β1 integrin impaired ICl swell activation in skeletal muscle-derived C2C12 cells 55 . The integrin β chains seem to play a fundamental role in this context.…”
Section: Discussionmentioning
confidence: 99%